1984
DOI: 10.1002/1097-0142(19840901)54:5<951::aid-cncr2820540536>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Non-asbestos-related malignant mesothelioma. A review

Abstract: Malignant mesothelioma is an uncommon, but increasingly important, neoplasm. The existing English‐language medical literature concerning non‐asbestos‐related malignant mesotheliomas was reviewed for evidence of other agents associated with the induction of malignant mesothelioma. Both animal and human data were reviewed. In most reviews of malignant mesothelioma, there are a significant proportion of cases without documented asbestos exposure (range, 0% to 87%). Furthermore, there are several fairly well‐docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
76
0
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(83 citation statements)
references
References 48 publications
3
76
0
4
Order By: Relevance
“…20 A variety of other causes of mesothelioma have been suggested based on case reports and animal studies, including therapeutic radiation. [21][22][23][24][25][26][27][28][29][30][31] There have been many case reports of mesothelioma after radiotherapy for various diseases, and the most numerous have been related to HL. [32][33][34][35][36][37][38][39] To our knowledge, the only epidemiology study to date that examined whether radiation increased mesothelioma rates in HL survivors followed 13,743 patients from 1973 to 1993 and reported no cases of mesothelioma.…”
mentioning
confidence: 99%
“…20 A variety of other causes of mesothelioma have been suggested based on case reports and animal studies, including therapeutic radiation. [21][22][23][24][25][26][27][28][29][30][31] There have been many case reports of mesothelioma after radiotherapy for various diseases, and the most numerous have been related to HL. [32][33][34][35][36][37][38][39] To our knowledge, the only epidemiology study to date that examined whether radiation increased mesothelioma rates in HL survivors followed 13,743 patients from 1973 to 1993 and reported no cases of mesothelioma.…”
mentioning
confidence: 99%
“…The association between mesothelioma and asbestos exposure was first reported by Wagner et al [9] in 1960. However, the relationship between peritoneal mesothelioma and asbestos is less obvious than that of pleural mesothelioma [10] . Liu et al [6] also have reported a non-asbestos-related primary mesothelioma of the greater omentum.…”
Section: Discussionmentioning
confidence: 99%
“…También se ha detectado mediante el método de Western-blot anticuerpos anti-Tag en el suero de estos pacientes. 24 Al mismo tiempo, varios autores han seguido de forma retrospectiva a estos pacientes tratados con vacunas contaminadas, sin que hasta la fecha se haya registrado una mayor incidencia en la aparición de mesoteliomas y osteosarcomas. 29 Algunos autores mencionan la existencia de otros virus como BKV, 24 que actuarían como cofactores del SV40, mientras que otros relacionan el potencial cancerígeno del virus SV40 con su capacidad para interactuar, por medio de su oncoproteína (Tag), con proteínas supresoras del crecimiento como la P53, inactivándolas y favoreciendo así la aparición del MM.…”
Section: Discussionunclassified
“…24 Al mismo tiempo, varios autores han seguido de forma retrospectiva a estos pacientes tratados con vacunas contaminadas, sin que hasta la fecha se haya registrado una mayor incidencia en la aparición de mesoteliomas y osteosarcomas. 29 Algunos autores mencionan la existencia de otros virus como BKV, 24 que actuarían como cofactores del SV40, mientras que otros relacionan el potencial cancerígeno del virus SV40 con su capacidad para interactuar, por medio de su oncoproteína (Tag), con proteínas supresoras del crecimiento como la P53, inactivándolas y favoreciendo así la aparición del MM. 30 Estamos seguros de que los resultados obtenidos en este estudio representan un primer acercamiento para planear investigaciones prospectivas que tomen en cuenta análisis bioquímicos y moleculares más específicos, encaminados a establecer asociaciones con la patogénesis de la enfermedad.…”
Section: Discussionunclassified